"Having regard" to intoxication in the Sexual Offences Act 2003 - an analysis of the mens rea in the Sexual Offences Act, and the meaning of circumstances - Cann, W (Sweet & Maxwell, 2024)
This article challenges the prevailing view in relation to sexual offences, that the defendant’s intoxication is not relevant when applying the “reasonable belief in consent” provision. It argues that, as a matter of statutory interpretation, intoxication may be considered a “circumstance” under Section 1(2) of the Sexual Offences Act 2003, utilising evidence from other common law jurisdictions. The role of the phrase “having regard to” is examined, concluding that this phrase prevents the undesirable consequences of holding intoxication to be a circumstance. Several fact patterns are given along with a normative justification which illustrates the requirement for the law to develop in this area.